2013
DOI: 10.1259/bjr.20130281
|View full text |Cite
|
Sign up to set email alerts
|

The role of pre-treatment diffusion-weighted MRI in predicting long-term outcome of colorectal liver metastasis

Abstract: Objective: To determine the prognostic value of pre-treatment apparent diffusion coefficient (ADC) of colorectal liver metastases in predicting disease response, progression-free survival (PFS) and overall survival (OS). Methods: We retrospectively reviewed 102 patients who underwent pre-treatment diffusion-weighted MRI using a breath-hold (b50, 150, 500) or a free-breathing (b50, 50, 100, 250, 500, 750) technique. The mean ADC (b50-500) and mean flow-insensitive ADC (ADC high ) values (breathhold: b5150 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
4
27
0
Order By: Relevance
“…Some previous studies have already shown that lower pretreatment ADC values were linked to short-term tumorsize reduction of single CRC liver metastases undergoing chemotherapy, whilst being unable to predict final patient outcome (Cui et al 2008;Tam et al 2013). Both animal models and clinical studies have shown that necrotic lesions exhibit higher ADC values (Herneth et al 2003;Kokabi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have already shown that lower pretreatment ADC values were linked to short-term tumorsize reduction of single CRC liver metastases undergoing chemotherapy, whilst being unable to predict final patient outcome (Cui et al 2008;Tam et al 2013). Both animal models and clinical studies have shown that necrotic lesions exhibit higher ADC values (Herneth et al 2003;Kokabi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Making this distinction would enable repeat treatment or alternative therapy if necessary. Furthermore, given the significant impact and adverse effects of current treatments, including chemotherapy and LRT, knowledge of how likely a lesion is to respond to therapy will also facilitate clinical decision-making in terms of how aggressively to pursue treatment 8 .…”
Section: Liver Applicationsmentioning
confidence: 99%
“…Furthermore, liver metastases with low pre-treatment ADC values have responded better to systemic chemotherapy compared to lesions with high pre-treatment ADC values in several series. High pre-treatment ADC value of liver metastases is therefore a potential predictor of poor response to chemotherapy 8,129,132 . Metastatic lesions with higher ADC values may in fact have diminished blood supply and consequentially, more baseline cellular hypoxia and necrosis, which may limit the effectiveness of therapy.…”
Section: Liver Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Of late, DWI has been introduced for the differentiation of benign and malignant lesions in extracranial organs, especially for diagnosis of abdominal and pelvic organs. 20,21 Although multiple previous studies have discussed the feasibility of DWI in detecting and diagnosing cervical cancer, 22-24 the findings are inconclusive or conflicting. Thus, we undertook a meta-analysis to evaluate the possible benefit of DWI to differentiate metastatic from non-metastatic LNs in uterine cervical cancer.…”
mentioning
confidence: 99%